Tutkimusympäristö muutoksessa: Tutkijoiden näkemykset SHOK:n, korkeakoulukeksintölain ja yliopistolain vaikutuksista - Antti-Jussi Tahvanainen; Tuomo Nikulainen (The Research Institute of the Finnish Economy (ETLA), 2010)
This study examines the researcher's perspective on the impact of recent major changes in the Finnish research environment. Three virtually simultaneous changes are of special importance. The first is the on-going renewal of the Universities Act governing the Finnish higher education system in its entirety. The second change is the foundation of the so-called Strategic Centres for Science, Technology and Innovation that aim at establishing and re-enforcing long-term research cooperation between the academia and the Industry. The final change is the enactment of the new University Inventions Act in early January 2007. Surveying the opinions of roughly 1700 researchers active in different fields of science and working at 11 different Finnish research universities, the study aims to map the experiences of researchers regarding the reform-induced changes in the operational environment and implementation of research. In general the study concludes that all three reforms have been pessimistically received among the respondents. Benefits related to alleged improvements in the preconditions for academic research, in particular, elicited strong disagreement. Researchers anticipate a swell in administrative burden, and do not believe in a general increase in the quality of research. In addition, claims related to increases in the lengths of research projects and funding cycles are rejected systematically. Instead, researchers believe that the reforms promote commercialism in the university environment. This does not entail greater incentives for researchers to participate in the commercialization of their research outputs, however. Such claims were largely rejected by the respondents. The pessimistic results convey the impression that the commercialization of the university environment is being implemented at the cost of academic research.
Keywords: O30; O38; O33; O34; 330; Innovation system; Universities Act; University Inventions Act; Strategic Centres for Science; Technology and Innovation; research environment; innovation policy